Nuclear cGAS suppresses DNA repair and promotes tumorigenesis. (1st November 2018) - Liu, Haipeng; Zhang, Haiping; Wu, Xiangyang; Ma, Dapeng; Wu, Juehui; Wang, Lin; Jiang, Yan; Fei, Yiyan; Zhu, Chenggang; Tan, Rong; Jungblut, Peter; Pei, Gang; et al.
Abstract Accurate repair of DNA double-stranded breaks by homologous recombination preserves genome integrity and inhibits tumorigenesis. Cyclic GMP–AMP synthase (cGAS) is a cytosolic DNA sensor that activates innate immunity by initiating the STING–IRF3–type I IFN signalling cascade1, 2 . Recognition of ruptured micronuclei by cGAS links genome instability to the innate immune response3, 4, but the potential involvement of cGAS in DNA repair remains unknown. Here we demonstrate that cGAS inhibits homologous recombination in mouse and human models. DNA damage induces nuclear translocation of cGAS in a manner that is dependent on importin-α, and the phosphorylation of cGAS at tyrosine 215—mediated by B-lymphoid tyrosine kinase—facilitates the cytosolic retention of cGAS. In the nucleus, cGAS is recruited to double-stranded breaks and interacts with PARP1 via poly(ADP-ribose). The cGAS–PARP1 interaction impedes the formation of the PARP1–Timeless complex, and thereby suppresses homologous recombination. We show that knockdown of cGAS suppresses DNA damage and inhibits tumour growth both in vitro and in vivo. We conclude that nuclear cGAS suppresses homologous-recombination-mediated repair and promotes tumour growth, and that cGAS therefore represents a potential target for cancer prevention and therapy. DNA damage induces translocation of cyclic GMP–AMP synthase to the nucleus, where it suppresses homologous recombination by interfering with the formation of the PARP1–Timeless complex.